The Portrait of Exclusion in Brazilian Universities: the limits of inclusion - Vinícius Neves de Cabral; Rosimeire Maria Orlando; Silvia Márcia Ferreira Meletti (Universidade Federal do Rio Grande do Sul, 2021)
The article aims to present a panorama of the access of disabled people to higher education in Brazil. For decades, public policies have promoted and advocated in favour of inclusive educational practices, but, despite some improvements, the educational system still seems to struggle to accommodate disabled students. Data were drawn from the databases of The Brazilian Institute of Geography and Statistics (IBGE) and of the National Institute for Educational Studies and Research Anísio Teixeira (INEP). As evidence shows, governmental measures have prioritised the expansion of private organisations, while the representation of disabled students in Brazilian universities remains a scenario of exclusion.